Space Charge and Electric Field Analysis on Contaminated XLPE Insulator - M.H.A. Wahab; N. A. M. Jamail; E. Sulaiman; Q.E. Kamarudin; N.A. Othman; S.M.N.S. Othman (Institute of Advanced Engineering and Science, 2018)
Nowadays, XLPE cable has been widely used because it has better resistance than other cables. XLPE insulation has unique features including a high dielectric strength and high insulation resistance. A lot of researches based on hardware and software have been conducted to prove the effectiveness of XLPE cable such as AC and DC applications and Space Charge Distribution measurement under HVDC at High Temperature. This research focused on analysis of space charge and electric field on XLPE cable with effect of non-uniform contamination layer by using Quickfield Software. Non-uniform contaminations have been applied along XLPE cable using Arsenic Tribromide (AsBr3), Boron Bromide (BBr3), Ethylene Dichloride (CH2C1), Formic Acid (CH1O2), Formamide (CH3NO) and Alcohol element. Presence of these contamination elements represent of underground contamination. The size and layer of the contamination were non-uniform type. From the results, it is shown that lower dielectric constant of contamination will affect more on charge of XLPE insulation. As a conclusion, it can be seen lower dielectric constant value of contamination element greatly affecting the performance of XLPE insulation. Furthermore, size of contamination also influences the content of charge in contamination where the bigger the contamination size, the more charge contained in the contamination.